The human nucleoporin Tpr protects cells from RNA-mediated replication stress - Kosar, Martin; Giannattasio, Michele; Piccini, Daniele; Maya-Mendoza, Apolinar; García-Benítez, Francisco; Bartkova, Jirina; Barroso, Sonia I; Gaillard, Hélène; Martini, Emanuele; Restuccia, Umberto; Ramirez-Otero, Miguel Angel; Garre, Massimiliano; et al. (Nature communications, 2021)
Although human nucleoporin Tpr is frequently deregulated in cancer, its roles are poorly understood. Here we show that Tpr depletion generates transcription-dependent replication stress, DNA breaks, and genomic instability. DNA fiber assays and electron microscopy visualization of replication intermediates show that Tpr deficient cells exhibit slow and asymmetric replication forks under replication stress. Tpr deficiency evokes enhanced levels of DNA-RNA hybrids. Additionally, complementary proteomic strategies identify a network of Tpr-interacting proteins mediating RNA processing, such as MATR3 and SUGP2, and functional experiments confirm that their depletion trigger cellular phenotypes shared with Tpr deficiency. Mechanistic studies reveal the interplay of Tpr with GANP, a component of the TREX-2 complex. The Tpr-GANP interaction is supported by their shared protein level alterations in a cohort of ovarian carcinomas. Our results reveal links between nucleoporins, DNA transcription and replication, and the existence of a network physically connecting replication forks with transcription, splicing, and mRNA export machinery.
Keywords: Protein Interaction Maps; HeLa buňky; poškození DNA; Intracellular Signaling Peptides and Proteins; transport RNA; replikace DNA; viabilita buněk; DNA Replication; HeLa Cells; acetyltransferasy; nestabilita genomu; Humans; DNA Damage; Acetyltransferases; Neoplasms; RNA Transport; Genomic Instability; Nuclear Pore Complex Proteins; mapy interakcí proteinů; komplex proteinů jaderného póru; intracelulární signální peptidy a proteiny; lidé; Cell Survival; protoonkogenní proteiny; Proto-Oncogene Proteins; nádory